2004
DOI: 10.1002/ajh.10465
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained bone marrow granulomas: Is amiodarone the culprit? A report of 2 cases

Abstract: Granulomas in the bone marrow are usually caused by infectious or hematological diseases, and drugs are only rarely implicated as causative agents. Recent reports have drawn attention to the role of amiodarone in the etiology of bone marrow granulomas. We report two cases of amiodarone-induced bone marrow granulomas in patients being investigated for refractory anemia and pancytopenia, respectively. Since both patients had life-threatening arrhythmias, discontinuation of the drug followed by rechallenge was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…7–13 In several reports, amiodarone was not stopped because the treating physicians determined that the cardiac benefits outweighed the potential hematologic risks. 9,11,12 Boutros et al 8 and Moran and Manoharan 10 observed an improvement in cytopenias that paralleled a partial or complete resolution of bone marrow granulomas by three to eight months after cessation of amiodarone. Mohamed et al 9 reported a patient with leukopenia and thrombocytopenia that improved by six months after discontinuation of amiodarone.…”
Section: Discussionmentioning
confidence: 94%
“…7–13 In several reports, amiodarone was not stopped because the treating physicians determined that the cardiac benefits outweighed the potential hematologic risks. 9,11,12 Boutros et al 8 and Moran and Manoharan 10 observed an improvement in cytopenias that paralleled a partial or complete resolution of bone marrow granulomas by three to eight months after cessation of amiodarone. Mohamed et al 9 reported a patient with leukopenia and thrombocytopenia that improved by six months after discontinuation of amiodarone.…”
Section: Discussionmentioning
confidence: 94%
“…This was attributed to amiodarone induced bone marrow granuloma through inhibition of phospholipases, leading to accumulation of phospholipids in bone marrow (Lossos and Matzner 1992). (Mukhopadhyay et al; suggested that granuloma formation occur due to immunological reaction. Other author (Chang and Ng, 2008) suggested that amiodarone initiate (erythropoietin) EPO-resistant anemia after treatment for arrhythmia which consequently cause decrease in RBCs synthesis and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Granulomatous bone marrow reactions have also been described in hematological malignancies, especially in Hodgkin and non-Hodgkin lymphomas but it is not clear if these findings are related to malignancy or infections (Table 1). [14][15][16]…”
Section: Discussionmentioning
confidence: 99%